2010
DOI: 10.4061/2010/529080
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation with Kidneys Affected by Tumours

Abstract: Renal transplantation confers improvement in quality of life and survival when compared to patients on dialysis. There is a universal shortage of organs, and efforts have been made to overcome this shortage by exploring new sources. One such area is the use of kidneys containing small tumours after resection of the neoplasm. This paper looks at the current evidence in the literature and reviews the feasibility of utilizing such a source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This may also explain why current evidence shows a relatively low recurrence rate from transplantation of resected kidney from small renal cancer donors [20]. A systematic literature review revealed 96 documented cases of renal transplants conducted with donor kidneys from small renal cancer patients, with no definite cancer recurrence [21].…”
Section: Discussionmentioning
confidence: 99%
“…This may also explain why current evidence shows a relatively low recurrence rate from transplantation of resected kidney from small renal cancer donors [20]. A systematic literature review revealed 96 documented cases of renal transplants conducted with donor kidneys from small renal cancer patients, with no definite cancer recurrence [21].…”
Section: Discussionmentioning
confidence: 99%
“…One such area is the use of kidneys containing small tumors after resection of the neoplasm. A report supports the feasibility of utilizing surgically restored cancerous kidneys [18]. In that report, the patients who had lost their kidney because of tumors supported the use of the kidneys (93%).…”
Section: Discussionmentioning
confidence: 81%
“…Several studies reported the detection of allograft renal cancer after transplantation . In 1971, Tunner reported a case in which a kidney with renal cell carcinoma was transplanted to an ESRF patient without resection of the tumor.…”
Section: Resultsmentioning
confidence: 99%